Preceptor Practice: Initial Results of a National Association for Nursing Professional Development Study. Issue 3 (May 2021) - Harper, Mary G.; Ulrich, Beth; Whiteside, Dawn; Warren, Joan Insalaco; MacDonald, Ryan
Abstract : In 2020, the Association for Nursing Professional Development commissioned a national preceptor practice analysis study using the Ulrich Precepting Model to identify the roles, knowledge, and activities essential to preceptor practice. In a survey of 3, 623 preceptors, the model's seven preceptor roles and their associated domains of knowledge and practice were validated. Findings indicate that nursing professional development practitioners should provide preceptors with initial role preparation in addition to ongoing education.